An evaluative study of the role of United States information service libraries in the Philippines - Adler, Alice Cecilia 1923- (1969)
In order to carry out these objectives, they provide free public library service available to everyone, and also try to reach special audiences with specialized collections. Because of shifting patterns of power and the high rate of literacy and education which broaden the base of potential leadership, it is important not to neglect the mass audience while making special efforts to reach small groups of opinion leaders.
The objectives of the USIS libraries are twofold : to disseminate information about the United States, its people and its culture; and to help explain and support specific U.S. foreign policy objectives.
The United States Information Service operates three libraries in the Philippines, in Manila, Cebu City and Davao City.
USIS libraries render a service which is unique in many ways, and does not duplicate what the local libraries are either trying to do or are in a position to do. Because the activities of the USIS libraries are geared to supporting U.S. foreign policy objectives, it is neither feasible nor appropriate to expect local libraries to assume these activities.
Vita.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Keywords: United States Information Agency; United States Information Service